2022
DOI: 10.1002/pmrj.12758
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of quantitative ultrasound measures of muscle in critically ill patients

Abstract: Background Quantitative neuromuscular ultrasound is increasingly used to study muscle pathology and changes in muscle mass during critical illness. Advantages of ultrasound are high axial resolution, low procedural risks, no ionizing radiation, and ease of use early in the course of disease. However, ultrasound is known to be an operator dependent imaging modality and the intensive care unit setting poses additional challenges to obtaining reliable measurements. There is limited evidence validating the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Finally, the muscles of the upper limb are less analyzed in relation to the quadriceps femoris. Our results corroborate the findings in the literature for the biceps brachii [18,32,33] and forearm flexors group [37]. There was less agreement, despite the excellent result, for interobserver reliability in the forearm flexor group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, the muscles of the upper limb are less analyzed in relation to the quadriceps femoris. Our results corroborate the findings in the literature for the biceps brachii [18,32,33] and forearm flexors group [37]. There was less agreement, despite the excellent result, for interobserver reliability in the forearm flexor group.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the muscles evaluated in this study, the quadriceps femoris is the muscle most analyzed in studies [5,17,18,33], probably because it has large dimensions and well-defined anatomical conditions, a fact that can make its assessment easier [17]. This study corroborates previous studies that demonstrated excellent inter-and intra-examiner reliability in assessing the quadriceps femoris in the ICU and with examiners with different levels of experience [5,17,18,33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…An ultrasound assessment may be a convenient, non-invasive tool to evaluate muscle wasting and quality, especially when assessing muscle thickness and echogenicity [ 45 , 46 ]. Here, our results demonstrated a high or very high intra- and inter-rater reliability for these two measurements.…”
Section: Discussionmentioning
confidence: 99%
“…As there were no previous normative data regarding muscle ultrasound values in hospitalized older patients, and also because our study was exploratory, we used information from previous research in Intensive Care Units to calculate the sample size. In the study from Baston et al, using Bland–Altman plots for inter-rater reliability, a measurement bias of 0.2 cm 2 for the cross-sectional area of avQRF was described [ 46 ], allowing us to use this surrogate measure as the minimum significant value to detect real differences between measurements. Accepting an alpha risk of 0.05 and a beta risk of 0.2 in a two-sided test, 157 subjects were necessary to recognize as statistically significant a difference greater than or equal to 0.2 cm 2 in the cross-sectional area of the avQRF.…”
Section: Methodsmentioning
confidence: 99%